RANCANG BANGUN ALFABET MEMORY GAME MENGGUNAKAN LINEAR CONGRUENT METHOD (LCM) - Sugeng Supriyadi (Universitas Kuningan, 2018)
AbstractThere are some algorithms that can be used to solve a problem, one of them is the Linear Congruent Method (LCM) algorithm. The linear congruent method algorithm is a random number generator algorithm that is widely used in computer programs. According to Zeenat Mahmood, et.al. (2012) the advantages of LCM are having speed, ease of implementation, and the availability of portable code, parameters and test results. While According to Dian Sekarsari (2014), the advantage of this algorithm is that its speed is good, because the operation is just a few bit manipulation operations. In PAUD Miftahul Huda Mekarmulya Village, the way of teacher in delivering alphabets recognition material is still conventional and it is less effective because it makes students become easily bored, less interested and students are less able to capture and receive alphabets recognition material delivered by the teacher. To improve students interest in learning then the writer designed an alphabets recognition game for children aged 4-6 years. Memory game is a game matching same pairs of images that have been randomized in the first order and the algorithm used to perform randomization on the composition of the image with linear congruent method algorithm. This research uses RUP system development method and this application is designed by using android studio tools. The results of this research are linear congruent method implementation, alphabet interface game memory and testing with black box and white box testing. This application is expected to help and increase the studentscuriousity in knowing and studying the alphabets. Keywords: Algorithm, Linear Congruent Method, Alphabets Introduction, Memory Game